Apoptosis and autophagy of muscle cell during pork postmortem aging - Chunmei Li; Xialian Yin; Panpan Xue; Feng Wang; Ruilong Song; Qi Song; Jiamin Su; Haifeng Zhang (Animal Bioscience, 2024)
Objective Pork is an important source of animal protein in many countries. Subtle physiochemical changes occur during pork postmortem aging. The changes of apoptosis and autophagy in pork at 6 h to 72 h after slaughter were studied to provide evidence for pork quality. Methods In this article, morphological changes of postmortem pork was observed through Hematoxylin-eosin staining, apoptotic nuclei were observed by TdT-mediated dUTP nick end labeling assay, protein related to apoptosis and autophagy expressions were tested by western blot and LC3 level were expressed according to immunofluorescence assay. Results In this study, we found the occurrence of apoptosis in postmortem pork, and the process was characterized by nucleus condensation and fragmentation, formation of apoptotic bodies, increase in apoptosis-related Bax/Bcl-2 levels, and activation of caspases. Autophagy reached its peak between 24 and 48 h after slaughter, accompanied by the formation of autophagosomes on the cell membrane and expression of autophagy-related proteins beclin-1, P62, LC3-I, LC3-II, and ATG5. Conclusion Obvious apoptosis was observed at 12 h and autophagy reached its peak at 48 h. The present work provides the evidence for the occurrence of apoptosis and autophagy during postmortem aging of pork. In conclusion, the apoptosis and autophagy of muscle cells discovered in this study have important implications for pork in the meat industry.